Sierra Leone : 2016 Article IV Consultation and Fifth Review Under the Extended Credit Facility and Financing Assurances Review and Request for an Extension of the Extended Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for Sierra Leone. (IMF Staff Country Reports; Country Report ;, 2016)
This 2016 Article IV Consultation highlights that economic outcomes in Sierra Leone have deteriorated sharply over the past two years. Growth declined dramatically from 20.7 percent in 2013, to 4.6 percent in 2014, and further to -21.1 percent in 2015. The budget is under severe pressure. Between mid-2014 and end-2015, the Leone depreciated 22 percent against the U.S. dollar. Banking sector vulnerabilities have increased. Living standards have also deteriorated significantly since late 2014. The medium-term outlook is somewhat positive, with growth projected to recover to 4.3 percent in 2016, increasing gradually to about 6.5 percent by 2020.